From rocking the cradle to rocking the system : women, community work and social change in Aotearoa : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy, Department of Social Policy and Social Work, Massey University - Craig, Wendy (Massey University, 1991)
This dissertation explores women's involvement in community work in Aotearoa. It is argued that women's significant contributions to community work have been hidden, devalued or ignored in mainstream writing and teaching. This study documents women's experiences and their perceptions of these experiences; such stories which are very seldom told. It also focusses on an explanation of social change from the perspective of women community workers. These women view community work as a site of struggle for change, through the processes of empowerment, self-determination and working collectively. Sixteen women, eight Maori and eight pakeha, participated in this study. These women have been identified as change agents and throughout their stories they constantly link their daily experiences to national, global and structural issues. All of the women have made a commitment to working towards change. This commitment has not always been been without cost to themselves and to their families. Although the changes that the women have achieved can, at times, be seen as reformist in nature, it is argued that as women's community work challenges the practices of the state, it contributes to social change processes. The approach taken is informed by my socialist feminist perspective. Issues pertaining to gender, race and, to some extent, class are considered in this thesis.. The study concludes that future theorising about community work in Aotearoa, must, of necessity show, more effectively how gender, race and class are interrelated. The differences between the Maori and pakeha women's stories indicate that gender cannot be examined in isolation from race. The existence of gender, as a category, is shaped also by other relations such as race and class. In articulating their struggles for change, the women reveal that there is much to be learned about the politics of caring. The women recognise that they have been trained to be the caregivers in society. For these women, however, caring plays an important role in the social change process. Their approach is based on an empowering model rather than a dependency one. Yet, whilst the women celebrate their own capacities related to caring, they are also concerned that men stand back from, and even devalue, this essential role which enables society to function. Thus community work is frequently conceptualised as women's work, and the women have to struggle to be recognised and paid for it. This thesis also shows that, despite the differences between the Maori and pakeha women, their relationship is generally co-operative and the potential for them to learn from one another exists. Through their collective involvement in the Aotearoa Community Workers Association the women have found ways to work towards a partnership which is based on an understanding of the rights of Maori as the indigenous people of Aotearoa. This research serves as a celebration of the women's experiences and knowledge of community work in Aotearoa. It is documented in a way that other women community workers can use to reflect on their own work. The challenge of any research and action is to not only record people's experiences, but also to use our knowledge, both written and oral, to provide an explanation of our current reality in order to , if necessary, change this reality. This dissertation, as part of a social process, has attempted to achieve this aim.
Keywords: Community work; Women and community work; Social change; Maori; New Zealand community work